PENGARUH WORKLOAD TERHADAP TECHNOSTRESS PADA PEKERJA DI BIDANG INDUSTRI MULTIMEDIA KREATIF DIGITAL - Salsabila Nur Sadrina Jamaluddin; Arfin Nurma Halida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid technological advancements including the emergence of tools such as Artificial Intelligence (AI) have greatly facilitated the work of professionals in the digital creative multimedia industry. However, the continuous pressure associated with technology usage can lead to